Depressed TFAM promotes acetaminophen-induced hepatotoxicity regulated by DDX3X–PGC1α–NRF2 signaling pathway - Sisi Chen; Yaling Cao; Zihao Fan; Ling Xu; Zhenzhen Pan; Yao Gao; Linlin Wei; Qiaoxin Wei; Yuan Tian; Xiangying Zhang; Mei Liu; Feng Ren (Molecular Medicine)
Abstract Background Acetaminophen (APAP)-induced acute liver injury (AILI) is the most prevalent cause of acute liver failure and mitochondrial dysfunction plays a dominant role in the pathogenesis of AILI. Mitochondrial transcription factor A (TFAM) is an important marker for maintaining mitochondrial functional homeostasis, but its functions in AILI are unclear. This study aimed to investigate the function of TFAM and its regulatory molecular mechanism in the progression of AILI. Methods The roles of TFAM and DEAD (Asp-Glu-Ala-Asp) box polypeptide 3 X-linked (DDX3X) in AILI were determined with TFAM overexpression and DDX3X knockdown, respectively. Results TFAM expression was suppressed in AILI patients. TFAM overexpression alleviated liver necrosis and mitochondrial dysfunction. Treatment of the AILI mice model with N-acetylcysteine (NAC), a drug used to treat APAP overdose, resulted in significant TFAM activation. In vivo experiments confirmed that TFAM expression was negatively regulated by DDX3X. Mechanistic studies showed that nuclear respiratory factor 2 (NRF-2), a key regulator of TFAM, was selectively activated after DDX3X knockdown via activated peroxisome proliferator-activated receptor γ coactivator 1 (PGC-1α), in vivo and in vitro. Conclusions This study demonstrates that depressed hepatic TFAM plays a key role in the pathogenesis of AILI, which is regulated by the DDX3X–PGC1α–NRF2 signaling pathway.